Factors Influencing Dividend Policy on Mining Companies Listed in Indonesia Stock Exchange 2011-2015 - Ingrit, Ingrit; Siregar, Hermanto; Syarifuddin, Ferry (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
The mining sector has an important role in economic development in Indonesia. Mining company has to have good responsibility to make investors trust in investing, especially in dividend policy. The dividend policy influenced by many factors such as micro and macroeconomics variables which influence investors to invest in mining companies. This research aims to examine the analysis of the current ratio, debt to equity ratio, return on assets, investment credit interest rate, exchange rate, mining stock price index and industrial production index toward the dividend policy. The samples used in this study are 10 mining companies listed in Indonesia Stock Exchange during the period 2011 to 2015. The significance influence test of independent variables is using panel data regression model with significant level (α) of 1%. 5% and 10%. Classic assumptions testing are conducted in order to obtain the best results including normality test, multicolinearity test, and heterocedasticity test. The result shows that the current ratio, debt to equity ratio, return on assets, investment credit interest rate, mining stock price index and industrial production index significantly toward dividend payout ratio. The results also show that the exchange rate is not a significant toward dividend payout ratio.